Effect of three dose levels of buffalo follicular fluid on estrus induction response in anoestrous goats - DAS, G K; AGARWAL, S K; BISHT, G S; SHANKER, UMA (The Indian Journal of Animal Reproduction, 2005)
The present study was designed to examine the effect of three dose levels of buffalo follicular fluid on estrus inductionresponse in anoestrous goats. A total of 40 aparently healthy and adult anoestrous does were equally divided into 4 groups i.e. G1,G2, G3 and G4• Ten does in each group were treated with charcoal (@ 5 mg/ml) extracted buffalo follicular fluid @ 12 ml (G1), 18ml (G2) and 24 ml (G,) through subcutaneous route twice daily for 3 consequitive days. Ten does were kept as. untreated control(G4). All the does following treatment were subjected to estrus detection at 12 hours interval. Total 16 (53.3%) out of 30 doesshowed estrus following buFF treatment. The proportion of does in estrus was higher (P > 0.05) in 18 ml (G2) as compared to 24ml (G,) (50%; 5/10) and 12 ml (G) (40%, 4/10) groups, respectively. None exhibited estrus in control group (GJ. The meaninterval between last buFF treatment to onset of estrus were 6.3:t:1.93, 6.4:t:1.17 and 7.6:t:0.87 days and developed estrus was18.0±3.46, 41.l:t:10.43 and 16.8:t:7.91 h in GI' G2 and G3 groups, respectively. The difference in mean duration of time taken foronset of estrus among the groups was not significant (P > 0.05). The results demonstrated the beneficial effect of charcoal treatedbuffalo follicular fluid for induction of estrus in anoestrus goats. Total dose of 18 ml buFF was found to be better for induction ofestrus in anoestrus goats.
Keywords: Buffalo follicular fluid; estrus; anoestrous goat